Human resource development management in improving the quality of educators at MTS Al Hikam Jatirejo - Istajib Charisun Ula; Abdullah Aminuddin Aziz; Mohamad Syahreza Pahlevi (Yayasan Azhar Amanaa Yogyakarta, 2023)
The research is intended to describe and analyze the management of human resources development at MTS al hikam jatirejo was inspired by jombang. To describe and analyze the quality of educators at MTS al hikam jatirejo was inspired by jombang. To describe and analyze the management of human resources development in improving the quality of educators at MTS al hikam jatirejo was inspired by jombang. The method used was case studies. Research shows that the management of human resource development at MTS al hikam jatirejo was debunked by jombang very well because it has been through several stages and selections made by madrassa head who refers to the vision of the madrasah mission and its prescribed standards of soup. The quality of educators at MTS al hikam jatirejo is detrained by jombang, and have effective roles and responsibilities, and the program evaluation results can be a model for the next program. The management of human resource development in enhanced educators at MTS al hikam jatirejo is said to be successful, with several such training as workshops, bimtech, and supervision to design and evaluate the development of human resources in the following year.